The Association of Real-World CA 19-9 Level Monitoring Patterns and Clinical Outcomes Among Patients With Metastatic Pancreatic Ductal Adenocarcinoma - George, Ben; Kent, Matthew; Surinach, Andy; Lamarre, Neil; Cockrum, Paul (Frontiers in Oncology, 2021)
Background: Pancreatic cancer is expected to be the third deadliest cancer in the US in 2021. Evaluation of treatment response in patients with mPDAC necessitates scheduled clinical and radiographic assessments along with monitoring serum CA 19-9 levels. Currently available single-institution data examining the importance of CA 19-9 monitoring cannot be generalized to real-world settings. We investigated the impact of serum CA 19-9 monitoring and its association with clinical outcomes in patients with mPDAC in a population-based setting. Methods: Data were extracted from the Flatiron Health electronic health record (EHR)-derived de-identified database for patients diagnosed with mPDAC between January 1, 2015, and June 30, 2020. Serum CA 19-9 levels at baseline – defined as the values obtained ≤ 60 days prior to treatment initiation - and during treatment were extracted. CA 19-9 levels > 40 IU/mL were considered elevated. Survival outcomes were compared based on testing frequency, baseline CA 19-9 levels, and change in CA 19-9. Results: 6,118 patients with mPDAC who received treatment were included in the analysis. The median age at diagnosis was 68 years (IQR: 61-75). Patients with normal baseline CA 19-9 experienced longer median survival than patients with elevated levels [1L: 8.8 months (95% CI: 7.9–10) vs 7.2 months (6.8–7.5), p < 0.001; 2L: 7.2 months (6.1–9.2) vs 5.2 months (4.9–5.6), p < 0.001; 3L: 6.1 months (5.4 – 9.1) vs 3.9 months (3.4 – 4.3), p < 0.001]. Patients with decreasing/stable CA 19-9 during treatment experienced longer survival than patients who experienced an increase in CA19-9 levels [1L: 10.9 months (10.5 – 11.3) vs 5.4 months (5.1–5.9), p < 0.0001; 2L: 8.2 months (7.7–8.5) vs 4.3 months (4.1–4.7), p < 0.001; 3L: 7.5 months (6.6–9.2) vs 3.7 months (3.4–4.3), p < 0.001]. Conclusions: In one of the largest, contemporary, real-world studies of patients with mPDAC, elevated CA 19-9 level at treatment initiation demonstrated a prognostic impact. Routine serial monitoring of CA 19-9 levels during treatment may be warranted, in addition to clinical and radiographic assessment, and may translate into better patient outcomes. Further validation studies are needed to understand the generalizability of these results.